Supramaximal interval training using anaerobic speed reserve or sprint interval training in rowers - Tongwu, Yu; Jinghui, Zhong; Chuanwei, Ding; Zijian, Zhang; Yuxiong, Xu (Frontiers in Physiology, 2025)
ObjectiveThis study aimed to compare the consistency of physiological adaptations and inter-individual variability in response to three distinct high-intensity interval training (HIIT) protocols—anaerobic power reserve (APR), maximal aerobic power (MAP), and sprint interval training (SIT)—among elite male rowers. By exploring the impact of individualized intensity prescriptions, we sought to identify the most effective protocol for enhancing training consistency, as well as improving both aerobic and anaerobic performance while minimizing variability in individual responses.MethodsThirty well-trained male rowers (mean age: 24.9 ± 3.1 years; height: 185 ± 4.4 cm; body mass: 86 ± 7.9 kg; body fat: 12.5% ± 2.4%) participated in the study. All participants were members of a national rowing team with an average of 6 years of competitive experience and regular participation in national and international championships. The intervention involved 6 weeks of individualized HIIT, performed three times per week, with pre- and post-tests assessing VO2max, cardiovascular efficiency (Qmax), anaerobic power (MSP, CP), and 2,000-m rowing performance.ResultsAll interventions resulted in significant improvements in VO2max, Qmax, MSP, and 2,000-m rowing time trial performance (p < 0.05). The SIT group exhibited the largest relative improvements, with VO2max increasing by 6.3% (from 51.9 ± 3.2 to 55.2 ± 3.3 mL·kg-1·min-1, Cohen’s d = 1.05, 95% CI [0.57, 1.53]), Qmax by 6.4% (Cohen’s d = 1.15, 95% CI [0.66, 1.64]), and a 3.7% reduction in 2,000-m time (Cohen’s d = 0.86, 95% CI [0.39, 1.33]). Notably, SIT demonstrated the lowest variability across all measured outcomes, as evidenced by reduced coefficients of variation and narrower confidence intervals.ConclusionThe SIT protocol, emphasizing maximal exertion, led to the most consistent adaptations and the greatest improvements across key performance metrics, including VO2max, Qmax, and 2,000-m rowing performance. These results suggest that SIT may be the optimal approach for improving performance consistency and maximizing physiological adaptations in elite rowers. Future research should explore the long-term applicability and potential integration of SIT with other training modalities to further enhance rowing performance.